Effect of industrial training on academic performance: evidence from Malaysia - Megat Mohd Nor, Putri Nor Suad; Ismail, Suhaiza (Penerbit UTHM, 2015)
This study aims to investigate the effect of industrial training on subsequent academic performance of accounting students in Malaysia. The performance measures examined in this study include the overall academic performance of the students as well as their performance in subsequent specific courses. In addition to the overall sample analysis, the study also investigates the impact on performance based on gender. This study uses secondary data obtained from the university database. In particular, the data on the list of accounting students who underwent practical training, information on GPA, CGPA, and the results for fundamental auditing, advanced auditing, fundamental taxation and advanced taxation courses for each student, are extracted from the database. The data are analysed using the Statistical Package for the Social Sciences (SPSS) software. In addition to the rudimentary statistical analysis techniques of mean score and standard deviation, paired-samples t-tests are conducted to examine the statistical significant impact of internship on performance for the overall sample as well as based on gender. The findings reveal that there is a statistically significant positive impact of internship on the academic performance of the overall accounting students for overall performance as well as for performance in auditing and taxation. For the analysis by gender, the results for the female group are consistent with the results of the overall analysis, whilst for the male counterparts, the results are mixed. To a large extent, there are no significant differences in the performance between males and females. The present study is one of the few studies that explores the impact of internship on academic performance in a developing country. Moreover, the study not only examines the impact on academic performance of overall students but also analyses the impact on gender basis.